Decolonizing Gender Identities in Indonesia: A Study of Bissu ‘The Trans-Religious Leader’ in Bugis People - Ismoyo, Petsy Jessy (UI Scholars Hub, 2020)
Bhinneka Tunggal Ika is one of the pillars of Indonesia that has placed our nation and nationess to a diversity of identity, from genders, tribes, religions, to cultures. Indonesia has a long history of gender diversity that recognized various gender identities as part of the culture. Henceforth, In Indonesia, gender is not perceived in a binary way between male or female, masculine and feminine, without giving the ‘third space’ to other genders and sexuality. For example, Bugis people recognize five genders: oroané, makkunrai, calabai, calalai, and bissu, which will be examined further in this paper. In reality, a lively debate emerges about “gender pluralism” that is considered not part of Indonesian culture. The rising number of persecution to the minority, including transgender people, has placed them to the most vulnerable groups because of their gender identity. This paper aims to deconstruct the understanding of gender identities in Indonesia through cross-cultural, socio-religious, and postcolonial approaches to develop the cultural history of gender pluralism in Indonesia. To examine further the decolonization of gender identities in Indonesia, the author identifies the process between ‘desire’ and ‘demand’ in terms of ‘The Colonizers’ and ‘The Colonized’ to see how the ‘dominant discourse represents reality about gender identities. By re-imagining ‘binary opposition’ in the ‘on-going’ process of movement happens in intercultural space, the author revives the ‘intersectional space’ of gender identities in Indonesia, as Edward Soja described ‘Third Space’. Research result showed that Bissu’s existence heretofore left ‘the conceived’ and ‘the Lived’ in the Bugis community; thus, it drifted the limited space given to the Bissu in ‘the perceived’. Consequently, it restricted the development of Bissu’s hybrid identity. Henceforth, the revival of malempu and malebbi were required as an intervention about giving back the power of agency within ‘sign games’ to the Bissu.